Indian migration to the Gulf : emerging challenges and prospects - Rahman, Anisur, 1964-; P. A., Ansari; Babu M., Sameer (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book explores issues of rights, issues and challenges faced by Indian migrant workers in GCC countries. It focuses on the struggle of migrants in the state of origin and destination states and how the process of migration shapes the identity and existence of migrant workers. The essays in the volume focus on policy, rights, issues, and challenges faced by the migrants as well as the long-term challenges posed by the COVID-19 pandemic. With contributions from academics and policymakers, this book will be of interest to scholars and researchers of migration and diaspora studies, public policy, and South Asian Studies"--
Indian diaspora in Gulf : impacts and advantages / Javed Charan -- Impact of COVID-19 on Gulf return migrants to India : a study of Kerala / Ansari PA, Sameer Babu M, and Anisur Rahman -- Nature process and consequences of migration : a case study of migration from India to Gulf / Mohammed Taukeer -- Emigration and changing lifestyle among skilled Indian professionals in the Gulf Region : a socio-cultural perspective / Ani Merly Paul and Lekshmi S Kaimal -- Expatriate organizations and social capital : the case of Kerala Muslim Cultural Centre (KMCC) / Muhammed Shabeer T -- India-GCC countries connection : trends, perspectives and opportunities / Bhupesh -- Gulf migration, remittances and development : the Indian experiences / Anisur Rahman and Waseem Ahmed -- Family tax, Indian expatriates and the Saudi economy / Muhammad Azhar -- Are remittance inflows good for economic growth? : evidence from India to the Gulf using linear ARDL approach / Shahid Bashir and Mohsin Majeed -- The COVID-19 crisis and migration : impact on Kerala economy / Muhammed Fazal -- Migration from Punjab to Gulf countries : Punjabi migrants and social change in left behind women / Atinder Pal Kaur -- Mobility in the margin experience of migration and development in Kerala, India / Jafar -- Socio-cultural milieu as a decisive factor of Goan migration to the Gulf / Sonal Thakker -- Pangals migration in Gulf countries / Md. Chingiz Khan -- Migration in Kerala : prospects and challenges with special reference to return migration / Baby Kizhakkekalam and Jyothi KK -- Indian female migrant workers and human rights violations in the Gulf : a case study of Kuwait / Naziya Naweed -- Studies on migration to Gulf countries : a review of current Indian literature / Deepa -- Indian 'guest workers' in the Gulf : discussing Deepak Unnikrishnan's temporary people / Nitesh Narnolia and Mousam.
OCLC-licensed vendor bibliographic record.
Keywords: Foreign workers, East Indian -- Persian Gulf States; East Indians -- Persian Gulf States -- Social conditions; Emigrant remittances -- India; Return migration -- India; India -- Emigration and immigration; Persian Gulf States -- Emigration and immigration; SOCIAL SCIENCE / Emigration & Immigration; SOCIAL SCIENCE / General